THE IMPLEMENTATION OF STRATEGIC MANAGEMENT ON COMPETITIVE ADVANTAGE IN ISLAMIC UNIVERSITY OF INDONESIA (UII) YOGYAKARTA - Nuryanta, Nanang (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2018)
This article aims to describe the implementation of strategic management on competitive advantage in Islamic University of Indonesia (UII) Yogyakarta. There are two purposes in writing this article; firstly, to explain how the management of UII understands the concept of strategic management, and secondly, to seek for supporting factors which influence the implementation of strategic management on competitive advantage in UII. It is a qualitative research with case study approach. The respondents of this study are top management in UII like the Endowment Board Foundation as shareholders and UII's top management like rector and deans.